O papel do médico veterinário na prevenção da resistência bacteriana aos antimicrobianos: uma perspectiva de saúde única - Lopes, Gabriel Agostinho de Pádua (Universidade Estadual Paulista (Unesp), 2022)
Bacterial antimicrobial resistance is a subject of increasing importance in veterinary medicine. Antimicrobials are substances that exert selection pressure on bacteria, which can result in selection of bacteria that are resistent. Bacteria acquire resistance in various forms and use a range of mechanisms to evade the action of antimicrobial drugs. Because these drugs are used in humans, animals, and plants, it is advisable to approach this subject under a One Health perspective. There are notable differences in the way humans and animals are treated. In veterinary medicine, the inappropriate use of antimicrobial drugs can lead to the development of appearance antimicrobial resistance. The veterinarian has a fundamental role in the control and prevention of bacterial antimicrobial resistance, through actions that promote a precise diagnosis and improve animal hygienic conditions.

A resistência bacteriana aos antimicrobianos é um tema de crescente importância na medicina veterinária. Os antimicrobianos são substâncias que exercem pressão de seleção sobre as bactérias, levando à seleção de bactérias resistentes. As bactérias adquirem resistência de diversas formas e utilizam diferentes mecanismos para contornar a ação das drogas antimicrobianas. Pelo fato dos antimicrobianos serem utilizados nos seres humanos, nos animais e na agricultura, é aconselhável a abordagem do tema sob uma perspectiva de Saúde Única. Existem notáveis diferenças nas formas em que são tratados os seres humanos e os animais. Na medicina veterinária o uso inadequado de antimicrobianos pode contribuir com o desenvolvimento da resistência bacteriana. O médico veterinário possui um papel fundamental no controle e prevenção da resistência aos antimicrobianos através de ações que promovam um diagnóstico preciso e melhorem as condições de higiene dos animais.
The role of the veterinarian in the prevention of antimicrobial resistance: a one health perspective
Keywords: Bacterial resistance; Antimicrobials; One health; Veterinary medicine; Resistência bacteriana; Antimicrobianos; Saúde única; Medicina veterinária; Prevenção; Prevention